COVID-19 in cancer patients with diabetes in Pakistan: Clinical features and management - Asghar, Kashif; Abu Bakar, Muhammad; Ashfaq, Sara; Alvi, Asim Munir; Shafiq, Waqas; Azmat, Umal; Siddiqi, Ahmed Imran; Farooq, Asim; Raza, Rabail; Siddique, Kashif (Frontiers in Oncology, 2022)
Background: Diabetes and cancer are the leading causes of mortality all over the world. Infectious diseases are more common and/or life-threatening in patients with diabetes. Cancer patients with diabetes are individuals that are more susceptible to the current COVID-19 pandemic. We investigated the clinical features of survivor and non-survivor COVID-19-infected cancer patients with diabetes. Patients and Methods: We did a retrospective study of 43 diabetic cancer patients with PCR-confirmed COVID-19 infection from Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan between March 03, 2020, and May 18, 2021. These patients either were discharged from the hospital or had died by Jun 16, 2021. Clinicopathological and radiological features were compared between survivors and non-survivors by fisher’s exact test and chi-square test. Results: Forty-three diabetic cancer patients with SARS-CoV-2 infection were enrolled and the majority were males 26 (60.5%). The overall mean age was 61.67 ± 11.80. 39 (90.7%) had solid tumors and 3 (7.0%) had hematological malignancies. Fever (74.4%) and dyspnea (58.1%) were the most common symptoms. Complications were reported in 36 (83.7%) patients; during the course of the disease. Additionally, 15 (100%) of 43 patients having complications were non-survivors. 11 (25.6%) patients were admitted to an intensive care unit (ICU). Furthermore, 29 (67.4%) out of 43 patients showed abnormal features in the radiological findings. We found significantly elevated levels of C-reactive protein (P=0.005), serum lactate (P=0.01), albumin (P=0.02), alkaline phosphate (P=0.03) and neutrophil count (P=0.04) in the non-survivors as compared to the survivors. Conclusion: Cancer patients with diabetes are a vulnerable population in the current pandemic. Identifying how diabetes in cancer patients affects the severity of SARS-CoV-2 infection is crucial for the clinical management of these patients. Rigorous scrutiny of clinicopathological features of COVID-19 infected cancer patients with diabetes especially values of C-reactive protein, lactate, albumin, alkaline phosphate, neutrophils and regular monitoring of blood glucose levels may play a critical role in the outcome of the disease.